Церква як євхаристійне спілкування - Возняк, Ореста; Vozniak, Oresta (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті розкрито сутність православної Церкви як спілкування в Христі, тобто – як власне євхаристійне спілкування. При цьому підкреслено суголосність еклезіологічної проблематики діалогічній традиції у філософії. Саме спілкування фіксує онтологічну та конститутивну засаду співбуття, внутрішню вкоріненість особистості в іншому, потребу в іншому Я як Ти. In this article there is revealed the essence of Orthodox Church as the intercourse In Christo that is the eucharistical intercourse. Herewith there is underlined the soundness of ecclesiological problems to dialogical tradition in philosophy. The communication fixes the ontological and constitutional foundation of coexistence, internal entrenchment of personality in another, the need in another ego as You. The revelation and clear witnessing of eucharistical dimension of the church life reveals the groundlessness of such type of Christian presence that is connected with supremacy and authoritarian unification under the aegis of unique ideology.
Church as Eucharistical Intercorse
Keywords: комунікація; спілкування; діалогічна філософія; Церква; євхаристія; єдність; communication; intercourse; dialogic philosophy; Church; Eucharist; unity